RANCANG BANGUN E-COMMERCE PADA TOKO BAJU WANITA DENGAN MENGGUNAKAN METODE WATERFALL - Ayu Purnama Sari; Sulistiyono Sulistiyono; Imam Akbar Refina; Dwi Bayu Rendra (Universitas Pahlawan Tuanku Tambusai, 2022)
In the current era of globalization, the use of the internet which leads to the business world has begun to use the internet as a medium of sale and purchase. Merchandise_yensu22 clothing store, currently marketing and selling is still conventional. Merchandise_yensu22 clothing store is a business that is engaged in clothing where the purchase of products from consumers is done by directly coming to the store. To expand sales, this business unit began to follow the development of information technology, especially in online marketing and sales activities, namely through an online store website (E-Commerce) where buyers can come from many regions. In the research conducted using the software development method, namely the Software Development Life Cycle (SDLC Waterfall) method and using data collection techniques such as observations, interviews, and literature studies. Website application design at the Dagangan_yensu22 clothing store uses software such as XAMPP, STAR UML, NOTEPAD ++, and uses the PHP programming language and uses the IGNITER CODE Framework. Testing this website, buyers can see and buy their products without having to come directly to the store. Keywords: E-Commerce, Website, Merchandise Shop_yensu22, Waterfall